Analisis Etika Bisnis Islam Terhadap Kegiatan Ekonomi (Studi PAda Usaha Depot Air Minum Pondok Pesantren Pancasila Bengkulu) - Agasi, Alfiyyah; Isnaini, Desi; Cahyono, Andi (Indonesian Journal of Islamic Economics and Business, 2025)
This study aims to analyze the application of Islamic business ethics in economic activities at the refill drinking water depot of Pancasila Islamic Boarding School in Bengkulu. The research focuses on production, distribution, and consumption aspects, using a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving 10 informants consisting of the management, employees, and consumers. The results show that the implementation of Islamic business ethics is fairly good, reflected in efforts to maintain product halalness, fair pricing, and consumer satisfaction. However, some challenges remain, such as machine maintenance, water quality testing, and limited marketing reach. The study finds that applying Islamic business ethics strengthens public trust, enhances economic independence, and promotes a sustainable business model aligned with Islamic values. The novelty of this study lies in its exploration of how Islamic ethical principles can support pesantren-based entrepreneurship to achieve both spiritual and economic sustainability.